NORDIC COOPERATION IN CULTURE AND EDUCATION - V. S. Vodopyanov (Vestnik MGIMO-Universiteta)
The article is dedicated to the Nordic cooperation in culture and education as a basis of the subregional integration. Nordic countries actively develop interaction in these spheres today both because of the common historical and cultural roots and values and due to pragmatic reasons. Thus, it performs an important utilitarian function by serving the needs of the common labour market in the Nordic region, which faces challenging problems, such as low birth rates and aging of the population. It is formation and development of the common cultural, linguistic, educational, and social space that increase the effectiveness of the Nordic labour market. Special attention in the article is paid to specific tools and forms of cooperation in culture and education aimed at expert personnel training and easy enculturation of Nordic citizens in any country of the region. Wide range of instruments includes co-funded specialized organizations, committees, inter-state cultural funds, theme-based cultural programmes, regional projects and mobility projects, Northern cultural forums, the Nordic Council Prize, etc.